أثر النصوص الشرعية في تأصيل القواعد الأصولية المتعلقة بالسنة - البرزنجي, صباح محمد نجيب; البرزنجي, صباح محمد نجيب (Sulaimani Journal for Humanities, 2018)
There is no doubt that the study of fundamentalist rules (Al- qawaid al- usolya) is of great importance, because the fundamentalist rules are considered as the foundations and laws upon which the Faqih and the Mujahid are based in order to reach the correct legal authority of the emerging issues. The linking of these rules to their legitimate sources of the Quran and Sunnah makes them more effective. Scientists have. In this research we discussed the fundamental rules related to the Sunnah, and mentioned the views of the scholars on the validity of these rules. Then we listed the shar'i texts of the Qur'aan and Sunnah, which can be inferred from the validity of these rules.